The binding of berenil to Escherichia coli ribosome. - Sinharay, S (1977)
The binding of the nonintercalating dye berenil to the 70S ribosome of Escherichia coli has been demonstrated by spectrophotometric measurements and gel filtration through Biogel P100 column. The berenil spectrum is gradually shifted towards the red region with the increasing amount of ribosome added, the isosbestic point being at 375 nm. There is positive cooperativity in the binding of berenil to the ribosome as demonstrated by the equilibrium dialysis. On binding with berenil, the ribosome is degraded faster by RNase I especially at low Mg++ concentration and its capacity to inhibit RNase I catalysed hydrolysis of ribopolymers is decreased. These indicate the unfolding of the structure of the ribosome.